ANALISIS STATISTIK DAN PROBABILITAS MASA DINAS KEPALA SEKOLAH DAN GURU DI WILAYAH KALIMANTAN MENGGUNAKAN METODE KAJIAN KEPUSTAKAAN - Faslih Fauji; Buna Rizal Nur Rohman; Daffa Tri Ananta; Muhamad Fazri Arizki (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
This research analyzes the service periods of school principals and teachers in four provinces in Kalimantan (Central Kalimantan, South Kalimantan, West Kalimantan, and North Kalimantan) to understand patterns and trends in the service periods of teaching staff. Years of service are an important indicator reflecting stability and continuity in the education system. Using a literature review and statistical analysis approach, this research examines the distribution of service periods through calculating frequency, mean value and cumulative frequency, and presents the results in the form of a histogram, polygon and ogive. The results show that the average length of service experience varies by province, from 7.7 to 12.8 years. The conclusions of this research suggest the importance of periodically evaluating service policy to ensure a balance between continuity and innovation in educational leadership, in order to support improving the quality of education in the Kalimantan region.